Risk of dementia and death in patients with atrial fibrillation: A competing risk analysis of a population-based cohort. (1st October 2016) - Marzona, Irene; Baviera, Marta; Vannini, Tommaso; Tettamanti, Mauro; Cortesi, Laura; Riva, Emma; Nobili, Alessandro; Marcon, Gabriella; Fortino, Ida; Bortolotti, Angela; Merlino, Luca; Roncaglioni, Maria Carla
Abstract: Background: Previous studies have stated that atrial fibrillation (AF) is associated with a higher risk of dementia. However, none have examined the competition between death and incident dementia in patients with AF. We evaluated the risk of incident dementia in patients with AF in comparison to people without this arrhythmia, considering of the competing risk of death. Methods: AF and non-AF cohorts were identified using the large administrative database of the Lombardy Region and followed for ten years. Patients with incident dementia were identified if they had an ICD 9 code referring to dementia at hospital discharge or a prescription for any anti-dementia drug. The association of AF with dementia or death was assessed with the multivariable Cox proportional-regression model, sensitivity analysis with a 1:1 propensity score matching and competing-risk analysis. Results: In 2003 a total of 27, 431 patients were hospitalized for AF in the Lombardy Region, while the cohort of non-AF counted 1, 600, 200 people. AF was associated with a higher risk of dementia (17%) and death (51%) at multivariable Cox analysis. These results were confirmed by the model fitted after propensity score matching. However, competing risk analysis found the association between AF and incident dementia was no longer significant (HR 0.99; 95% CI 0.94–1.04). Conclusions: In this real-world population the association between AF and dementia was no longer statistically significant when death was considered a competing risk.